2021
DOI: 10.3390/ijerph18115885
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Warm-Up Protocol with and without Facemask-Use against COVID-19 on Cognitive Function: A Pilot, Randomized Counterbalanced, Cross-Sectional Study

Abstract: The present study aimed to verify the effect of a warm-up protocol with and without facemask-use on cognitive function. The sample was composed of 17 healthy, non-smoking physical education students (age = 17.6 years, height = 1.71 m, and body mass = 69.7 kg). They were randomized to perform 15 min of warm-up exercises, while wearing a cloth facemask (EXP) or no mask (CON) on two separate occasions, with at least 48-h separating conditions. Rate of perceived exertion (RPE) and d2 Attention assessment were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 26 publications
2
19
1
1
Order By: Relevance
“…Participants in the different conditions did not differ in RPE during the stepping task, which aligns with previous research from Shaw et al [ 12 ] and Epstein et al [ 10 ]. These results are different than some previous research demonstrating that the face masks had significantly higher RPE compared to no face mask following a warm-up protocol [ 16 ]. The current study had participants exercise until exhaustion, completing one task collecting RPE throughout, while Slimani and colleagues [ 16 ] had participants complete a warm-up comprised of multiple tasks (e.g., light tempo runs, arms circles, high knees jog, back kicking, and stretching exercises) and collected RPE before and after each session.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Participants in the different conditions did not differ in RPE during the stepping task, which aligns with previous research from Shaw et al [ 12 ] and Epstein et al [ 10 ]. These results are different than some previous research demonstrating that the face masks had significantly higher RPE compared to no face mask following a warm-up protocol [ 16 ]. The current study had participants exercise until exhaustion, completing one task collecting RPE throughout, while Slimani and colleagues [ 16 ] had participants complete a warm-up comprised of multiple tasks (e.g., light tempo runs, arms circles, high knees jog, back kicking, and stretching exercises) and collected RPE before and after each session.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, scholars have examined how face coverings impact the rating of perceived exertion (RPE) but report inconsistent findings [ 10 , 12 , 13 , 16 ]. In one study examining the impact of face masks on RPE and cognitive function, Slimani et al [ 16 ] reported that the face mask condition had significantly higher RPE compared to no face mask following a randomized 15-min warm-up protocol. Moreover, the face mask condition in the research of Slimani et al [ 16 ] experienced significantly higher increases in concentration performance compared to no face mask condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors even hypothesize that mask application might result in headache, impaired cognition 17 , or in cardiac or renal overload 18 without providing clear evidence. Contrastingly, no detrimental reductions in well-being and performance 19 and even positive effects of mask wearing during exercise on cognitive function 20 were reported by early RCTs. It is of utmost importance to further evaluate these effects in order to prove that mask application during daily living does not lead to detrimental health consequences.…”
Section: Introductionmentioning
confidence: 87%
“…Information about the effects of facemask on physiological and cognitive functions during exercise is limited ( Shaw et al, 2021a ; Slimani et al, 2021 ). It seems that wearing a mask during exercise imposes extra pressure on ventilation ( Hopkins et al, 2021 ), which may lead to small changes in physiological parameters, such as increased dyspnea, end-tidal CO 2 , heart rate and respiratory rate ( Shaw et al, 2021b ; Hopkins et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%